Agricultural cooperatives in AP Vojvodina - position, potentiality and perspectives - Nestorov Bizonj, Jelena; Potrebić, Velibor; Arsenijević, Željko (Economics of Agriculture, 2010)
This paper discusses some of the basic data which define the current situation, potentials and prospects of agricultural cooperatives in A. P. Vojvodina. Agricultural cooperatives are a key factor in sustaining and improving the competitiveness of agricultural producers, in terms of increasing competition, which occurs as a result of the approaching process to the European Union. The potential of agricultural cooperatives in the past and the present has not been adequately exploited - for many reasons - some of which are the primary legislative framework is inadequate, and the system and economic position of cooperatives in economic policy in agriculture, but also the overall economic policy. Prospects of agricultural cooperatives are conditioned by the creation of adequate legal, institutional and economic environment for their business, which will significantly influence the effects of the cooperative organization of agricultural producers.